Drying kinetics and quality analysis of black turmeric (Curcuma caesia) drying in a mixed mode forced convection solar dryer integrated with thermal energy storage. (May 2018) - Lakshmi, D.V.N.; Muthukumar, P.; Layek, Apurba; Nayak, Prakash Kumar
Abstract: Performances of a mixed mode forced convection solar dryer integrated with paraffin wax based thermal energy storage have been studied for drying the sliced black turmeric ( curcuma caesia ). Thin layer drying kinetics of sliced black turmeric dried in a solar dryer has been compared with the open sun drying. Two 200 g samples of black turmeric were chosen and one was placed in the solar dryer and another was placed in the open sun. The samples were dried from initial moisture content of 73.4% (w.b) to 8.5% (w.b) in 18.5 hr in the solar dryer and the sample took 46.5 hr in open sun drying. Ten thin layer drying kinetic models were fitted with experimental data and Two term model and Page model were found to be best suited for predicting the drying kinetics of sliced black turmeric dried in the solar dryer and in open sun, respectively. The overall solar air heater efficiency and the overall solar dryer efficiency were found to be 25.6% and 12.0%, respectively. Quality analyses of fresh, solar dried and open sun-dried samples were also carried out in terms of colour, anti-oxidant activity, and flavonoids. Highlights: A mixed mode forced convection solar dryer with thermal storage has been developed. Drying kinetics of black turmeric has been investigated. Over all drying efficiency of the system was 12%. Developed solar dryer saves 60% of drying time compared to open sun drying. Quality analyses of samples dried in solar dryer and open sun drying are presented.